Para-anal lipoma as a rare consequence to perineal trauma. Case-report and review of the literature. Issue 6 (2nd November 2019) - Uscilowska, Ewelina; Abbes Orabi, Nora; Léonard, Daniel; Mourin-Jouret, Anne; Libbrecht, Louis; Trefois, Pierre; Denis, Marie-Armelle; Bachmann, Radu; Remue, Christophe; Kartheuser, Alex
Abstract: Introduction: Lipomas are the most common benign mesenchymal tumors which can be found in any part of the body. Nevertheless, their etiology and pathogenesis remain unknown. It is hypothesized that some of these lesions could result from an acute or chronic trauma. Patients and methods: We report a case of a 54-year-old man presenting a perineal lipoma which volume grew rapidly after he fell on his buttock, in the context of inaugural epileptic seizure. Pelvic MRI showed a voluminous fatty mass, measuring 6.6 × 5 × 9 cm without any signs of local invasion. Furthermore, we review the latest research on lipomas originating from traumatic lesion. Results: The mass was completely excised in one block under general anesthaesia, using an elliptical incision and a deep dissection. We did not close the skin incision in view of the cutaneous defect. Post-operative recovery was uneventful and the patient was discharged from hospital two days after the operation. Histopathology indicated a reorganised lipoma with no evidence of malignancy. Conclusion: Perineal lipomas are extremely rare, pathological examination of imaging guided biopsies are needed to exclude malignancy especially a well-differentiated liposarcoma. MRI remains the first option and radical surgical excision is the gold standard treatment.